2021
DOI: 10.1017/wet.2021.46
|View full text |Cite
|
Sign up to set email alerts
|

Biologically effective dose of pyraflufen-ethyl/2,4-D, applied preplant alone or mixed with metribuzin on glyphosate-resistant horseweed in soybean

Abstract: Glyphosate resistance in weed species has presented immense challenges for farmers in Ontario. The co-application of burndown plus residual herbicides provides control of glyphosate-resistant (GR) horseweed control in soybean. Pyraflufen-ethyl/2,4-D is a premixed herbicide formulation sold under the tradename Blackhawk®. Five field experiments were conducted over a two-year period (2019, 2020) in fields in southwestern Ontario to ascertain the biologically-effective-dose of pyraflufen-ethyl/2,4-D, applied alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous research reported similar results when pyraflufenethyl/2,4-D was tank-mixed with other herbicides for GRCF control. Westerveld et al [42] reported no benefit in GRCF control when adding low rates of pyraflufen-ethyl/2,4-D (≤132 g ai ha −1 ) to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ); however, GRCF control was improved by 20% when greater rates of pyraflufen-ethyl/2,4-D (≥527 g ai ha −1 ) were added to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ) at 2, 4 and 8 WAA. In contrast to the present study, Westerveld et al [42] observed 87 and 95% decreases in GRCF density and biomass, respectively, when pyraflufen-ethyl/2,4-D (527 g ai ha −1 ) was added to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ), compared to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ).…”
Section: Control Of Glyphosate-resistant Canada Fleabanementioning
confidence: 99%
“…Previous research reported similar results when pyraflufenethyl/2,4-D was tank-mixed with other herbicides for GRCF control. Westerveld et al [42] reported no benefit in GRCF control when adding low rates of pyraflufen-ethyl/2,4-D (≤132 g ai ha −1 ) to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ); however, GRCF control was improved by 20% when greater rates of pyraflufen-ethyl/2,4-D (≥527 g ai ha −1 ) were added to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ) at 2, 4 and 8 WAA. In contrast to the present study, Westerveld et al [42] observed 87 and 95% decreases in GRCF density and biomass, respectively, when pyraflufen-ethyl/2,4-D (527 g ai ha −1 ) was added to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ), compared to glyphosate (900 g ae ha −1 ) + metribuzin (400 g ai ha −1 ).…”
Section: Control Of Glyphosate-resistant Canada Fleabanementioning
confidence: 99%
“…All other tankmixtures were considered additive. Westerveld et al (2021b) reported synergism when pyraflufen-ethyl/2,4-D (527 g ai ha -1 ) was added to glyphosate (900 g ae ha -1 ) plus metribuzin (400 g ai ha -1 ) applied PP in soybean 8 WAA.…”
Section: Glyphosate-resistant Canada Fleabane Controlmentioning
confidence: 99%
“…The suggested rate for tiafenacil use in dry bean crops is 25 to 75 g ai ha −1 . Westerveld (2021) reported comparable yield as the non-weedy plots with tiafenacil applied PP at 25 and 50 g ai ha −1 alone and in mixes with other herbicides in soybean. Similarly, another recent study has shown little injury with tiafenacil applied PP at 12.5, 25, and 37.5 g ha −1 in corn (Soltani et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tiafenacil is a new nonselective, pyrimidinedione, contact herbicide developed by FarmHannong Co., Ltd., in Korea, that is under consideration for use in corn, soybean, wheat, cotton, and other crops to control both monocot and dicot weeds prior to crop emergence (Anonymous 2020; Park et al 2018; Westerveld 2021). Tiafenacil is one of the most active protoporphyrinogen IX oxidase (PPO) inhibitor herbicides from the pyrimidinedione chemical family (Park et al 2018).…”
Section: Introductionmentioning
confidence: 99%